TANTANGAN PENDIDIKAN MORAL DI ERA DIGITAL: Strategi Pengajaran Dalam Menghadapi Perubahan Sosial Dan Teknologi - Nirmala Hidayati; Slamet Untung (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Digital transformation has brought about significant changes in the behavior, values, and social interactions of students, thus demanding a new approach in the process of moral education. This article will examine the various challenges in moral education in the digital era and analyze the teaching strategies that were successfully implemented by SMA Negeri 3 Pekalongan in responding to social changes and technological advances for students. Through a qualitative approach with a field study type (field research), the aim is to explore in depth various teaching strategies applied in the school with the main sources being the principal and Islamic Religious Education teachers as well as the main object being students. The results of the study showed that there was an increase in the morale of students at State Senior High School 3 Pekalongan through the application of the vision and mission, and habits that exist in the school, including the habit of shaking hands with teachers, morning prayers, congregational Dhuha and Dzuhur prayers, and morning studies. This moral improvement is manifested in the behavior of students who are more spiritual, responsible, tolerant, and demonstrate an attitude of mutual respect in social interactions. The active role of parents and the surrounding environment in students' morals will shape the character of students to be strong and have noble morals amidst the current of globalization